Christians and Jews in the twelfth century renaissance - Abulafia, Anna Sapir (Routledge, 1995)
Anna Abulafia probes the anti-Jewish polemics of twelfth century scholars who used new ideas to encourage persecution of the Jews and argued that the Jews had a different capacity for reason since they had not reached the "right...